The effect of technostress on online learning behaviour among undergraduates - Awang Kader, Mohd Aidil Riduan; Abd Aziz, Nurul Nadia; Mohd Zaki, Suhanom; Ishak, Maisarah; Hazudin, Siti Fahazarina (Universiti Utara Malaysia Press, 2022)
Purpose – Students’ incompetence to deal with the intricacies of technology during the teaching and learning process may have negatively affected their online learning process particularly throughout the COVID-19 pandemic. It is critical to research technostress influence on online learning behaviours among undergraduates. Thus, this research intends to examine the predicting factors that contribute to technostress and the correlation between undergraduates’ technostress and the behavioural intention to use online learning.